New Functions of Universities in Century XXI Towards "Fourth Generation" Universities - Miklós Lukovics; Bence Zuti (Transition Studies Review, 2015)
Nowadays, many successful examples prove that universities have a significant role in the enhancement of different regions. The competitiveness of regions is affected and altered by globalization and other background processes that serve as arrangers of regional structure and for this reason they deserve attention. The modern economic development demands that due to the increased engagement towards the society and economy, the traditional activities of the universities should be diversified. To be able to optimally exploit their potential regarding economic development, the presence of an outstanding educational culture it is necessary but not sufficient. It is also necessary to maintain high standards in quality regarding research activities and to promote the utilization of results in the local economy. Beyond the well-known typology of the first, second and third generation of universities that describe the above mentioned processes, the concept of the "fourth generation" of universities emerged in international literature that depicts interesting facts that are worth considering regarding the economic development activities of universities. The goal of this study is to review and systematize the active and passive activities of universities that enhance the competitiveness of a given region. We process the available ideas regarding the presence of "fourth generation" universities and we attempt to integrate these into the scientifically accounted framework of university generations.
Keywords: I20; I23; I25; R10; 330; Universities; Higher education; Economic development; Diamond-model